2018
DOI: 10.1155/2018/4534250
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Damage and Failure Mechanism of Rock under Combined Multiple Strain Rates

Abstract: During underground hard-rock mining, the drilling and blasting method currently remains the most economical excavation method, and the rock may experience a multistrain-rate spectrum under quasi-static, dynamic, and rheological loading conditions and their combination as well. The study on the damage mechanism of rock under multistrain-rate condition that induced by mining excavation is the fundamental issue for predicting the mining-induced hazards such as rockburst. In this study, the state of the art of roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 176 publications
(207 reference statements)
0
7
0
Order By: Relevance
“…Under static load, the loading speed was lower than that of crack propagation; hence, the Shock and Vibration saturated flowing water in the rock would have sufficient time to diffuse to the newly expanded crack. At the same time, the expansion of free water in the crack would produce a similar "siphon" effect and reach the crack tip, which played a role in lubricating the crack contact surface and promoted the crack growth [21]. However, under dynamic load, the crack propagation speed was much faster than that under static load, and free water had no enough time to expand into the crack during failure process.…”
Section: Static and Dynamic Compressive Strength Static And Dynamic mentioning
confidence: 99%
See 1 more Smart Citation
“…Under static load, the loading speed was lower than that of crack propagation; hence, the Shock and Vibration saturated flowing water in the rock would have sufficient time to diffuse to the newly expanded crack. At the same time, the expansion of free water in the crack would produce a similar "siphon" effect and reach the crack tip, which played a role in lubricating the crack contact surface and promoted the crack growth [21]. However, under dynamic load, the crack propagation speed was much faster than that under static load, and free water had no enough time to expand into the crack during failure process.…”
Section: Static and Dynamic Compressive Strength Static And Dynamic mentioning
confidence: 99%
“…Previous studies on the thermal damage of rock materials mainly focused on the effect of temperature on its static and dynamic mechanical properties [14][15][16], and the test results showed that both the P-wave velocity and density of rock decreased with the increase in temperature [17][18][19]. In addition, the static peak stress and elastic modulus decreased gradually with increasing temperature [20][21][22]. Ding et al [23] performed the uniaxial and triaxial compression experiments on sandstone from 20°C to 800°C and indicated that tensile and shear fractures formed during unloading at the lower initial confining pressure, while sliding of the microcracks occurred during unloading at the higher initial confining pressure.…”
Section: Introductionmentioning
confidence: 99%
“…To date, an increasing number of mines are entering the state of deep mining [1]. Unlike shallow mining, deep coal and rock masses always exist in the special mechanical environment of three highs and one disturbance, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive equations reflecting the inherent characteristics of rock has been a hot topic in the study of rock mechanics (Zhu et al., 2018). The damage evolution and fracture development of rock established on the basis of the constitutive model are increasingly valued by global scholars.…”
Section: Introductionmentioning
confidence: 99%